Sejarah Kuantitatif: Telaah Kritis tentang Teori dan Sejarah Abad XX - Abd. Rahman . (ETNOHISTORI: Jurnal Ilmiah Kebudayaan dan Kesejarahan, 2015)
The term ‘quatitative history’ covers a range of methodologies and theoreticalbases, linked by their reliance on numerical data. Allmost all historical writinginvolves quantification, however, whether implicit or explicit. Some strands ofquantitative history are not new fenomena. Malthus, for example, produced hisessay on population history in 1798, and economic history gained in importancefrom the mid-nineteenth century, partly due to the influence of Marx. During thetwentieth century, historians have increasingly wanted to study the mass ofpeople in the past rather than a few well-documented individuals. Frequently weneed to use quantitative methods to do so, thereby reducing a large amount ofdata to manageable proportion.